Translation, adaptation, and reliability of a Social Frailty Scale for the Brazilian context: a methodological study - Damasceno, Vanessa Almeida Maia; Zazzetta, Marisa Silvana; Orlandi, Fabiana de Souza (São Paulo Medical Journal, 2023)
BACKGROUND: Frailty comprises three dimensions: physical, psychological, and social. It is established that social frailty is correlated with several variables, such as quality of life, depression, and loneliness. These findings reinforce the need to investigate and define predictors of social frailty. OBJECTIVE: To translate, culturally adapt, and assess the reliability of the HALFT scale for Brazil. DESIGN AND SETTING: Methodological study conducted at Universidade Federal de São Carlos. METHODS: This study aimed to translate and culturally adapt the HALFT scale from English to Brazilian Portuguese, for which the steps of translation, synthesis of translations, back translation, evaluation by an expert committee, pre-test, and test-retest were followed. RESULTS: Two independent translators translated the HALFT. The consensual version was established by merging the translations, which were back translated into English by a third translator. The expert committee comprised seven health professionals working in frailty and/or social fields of study. Only one item on the scale had a content validity index of less than one (0.85). The instrument was pre-tested with 35 older adults who considered it clear and understandable, with no suggestion of changes. The reliability analysis (reproducibility) of the adapted version of the HALFT with test-retest of the scale with 23 participants showed a Kappa index of 0.62, showing good agreement. CONCLUSION: The HALFT scale is translated and adapted for Brazil, and shows good reliability. However, it is necessary to conduct psychometric analysis of the instrument to provide normative data for this population.